Power Bases and Informational Influence Strategies A Behavioral Study on the Use of Management Accounting Information - Heinemann, Patrick; SpringerLink (Online service) (Wiesbaden : Gabler Verlag : Imprint: Gabler Verlag, 2008)
Management accounting information serves as a primary information source for managers and is a powerful resource for strategic decision-making and influence processes on all organizational levels. Patrick Heinemann combines and extends the research on power and influence from social psychology with insights from scholarly works on the use of information. He derives hypotheses on the relationships between influence strategies based on management accounting information, influence outcomes, and various moderating variables. In a sample of top-level managers of a large German utility provider, the author tests these theoretical relationships using the Partial Least Squares approach to structural equation modeling. The results highlight the importance of understanding power relationships in organizations and the ways in which management accounting information can be used for successfully influencing subordinates.
Social Influence and Power -- Developing the Causal Model -- Methodological Conception -- Empirical Results -- Discussion -- Conclusion.
Keywords: Leadership; Business; Management science; Accounting; Bookkeeping .; Business Strategy/Leadership.; Business and Management, general; Accounting/Auditing.